2020
DOI: 10.1016/j.ebiom.2020.102722
|View full text |Cite|
|
Sign up to set email alerts
|

TRAF4 acts as a fate checkpoint to regulate the adipogenic differentiation of MSCs by activating PKM2

Abstract: Background: Mesenchymal stem cells (MSCs) selectively differentiate into adipocytes or osteoblasts, and several molecules control the fate determination of MSCs. Understanding these key checkpoints greatly contributes to the ability to induce specific MSC differentiation for clinical applications. In this study, we aimed to explore whether TNF receptor-associated factor 4 (TRAF4) affects MSC adipogenic differentiation, which we previously reported that could positively regulated the osteogenic differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
(77 reference statements)
2
21
0
Order By: Relevance
“…Since ubiquitination plays crucial roles in the onset and progression of cancer and metabolic syndromes (Popovic et al, 2014), we speculate that there might exist a correlation between ALKBH5 and ubiquitination in the regulation of physiological processes. In this regard, our current work links with reminiscent of a recent study that showed the TRAF4 expression levels were positively correlated with ALKBH5 in MSC (Cen et al, 2020). On the contrary, our result showed that the TRAF4 negatively correlated with ALKBH5 expression in 3T3-L1 cells.…”
Section: Discussionsupporting
confidence: 84%
“…Since ubiquitination plays crucial roles in the onset and progression of cancer and metabolic syndromes (Popovic et al, 2014), we speculate that there might exist a correlation between ALKBH5 and ubiquitination in the regulation of physiological processes. In this regard, our current work links with reminiscent of a recent study that showed the TRAF4 expression levels were positively correlated with ALKBH5 in MSC (Cen et al, 2020). On the contrary, our result showed that the TRAF4 negatively correlated with ALKBH5 expression in 3T3-L1 cells.…”
Section: Discussionsupporting
confidence: 84%
“…This makes it difficult for us to generate conditional knockout mice to study the effects of LYPLAL1-AS1 on adipogenesis in vivo. Based on the results from our study and other studies 52 , 53 , in vivo subcutaneous Matrigel plugs are a comparatively feasible method for testing the de novo adipogenesis ability of a lncRNA.…”
Section: Discussionmentioning
confidence: 62%
“…Repressive PPARĪ³ modulators acting as inverse agonists are suggested as promising therapeutic options in obesity management and are associated with enhancement in bone formation and improved WAT metabolic functions [ 9 , 48 , 59 , 60 ]. Furthermore, recent insights into the structural mechanisms of the PPARĪ³ repressive function [ 48 ] permit better understanding of the interpretation of the interactions between chemical ligands and PPARĪ³ protein.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the limited number of clinically available anti-obesity drugs [ 2 ], finding promising candidates for novel drug leads is on urgent demand. Development of effective treatments counteracting obesity is directed to several, indeed, overlapping approaches: (i) obstruction of excessive lipid accumulation and adipocyte hypertrophy [ 3 , 4 , 5 , 6 ]; (ii) resolution of the chronic inflammation in white adipose tissue (WAT) of the obese [ 7 , 8 , 9 ]; (iii) induction of metabolically healthy adipocyte recruitment [ 10 , 11 , 12 ]; (iv) promotion of energy expenditure through enhanced lipolysis, thermogenesis and browning of the WAT [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%